Synthesis of Zeolite/NPK Coated with Cu-Alginate-PVA-Glutaraldehyde as a Slow-Release Fertilizer - Ratna Betriani; Sutarno Sutarno; Indriana Kartini; Jolang Budiarta (Universitas Gadjah Mada, 2023)
The objectives of this study were to synthesize zeolite/NPK coated with Cu-alginate-PVA-glutaraldehyde as a material for slow-release fertilizers and to study the effect of various Cu concentrations in the coating material on the resistance of the zeolite/NPK fertilizer and to study the release rate reaction in citric acid. The study began with the synthesis of the zeolite/NPK fertilizer and the Cu-alginate-PVA-glutaraldehyde coating materials with variations of Cu concentration of 0.0; 0.2; 0.4; 0.6; 0.8; and 1.0 M. The Zeolite/NPK fertilizer and the coated NPK fertilizer were characterized by XRD and FTIR. The determination of the released N and P was conducted using a UV-Visible spectrophotometer, while released K and Cu was analyzed using AAS. XRD showed that the composite had a crystalline structure. The FTIR spectra showed characteristic cross-linking interactions between PVA-glutaraldehyde and Cu-alginate. A study of the release kinetics of zeolite/NPK coated with Cu-alginate-PVA-glutaraldehyde showed that increasing Cu concentration to 0.4 M decreased the amount of nutrition released, and the release process followed the pseudo-second-order kinetics. The release rate constants of N,P,K and Cu in the citric acid medium on zeolite/NPK coated with Cu 0.4 M were 8.49 × 10−3, 17.48 × 10−3, 21.73 × 10−3, and 8.57 × 10−3 mg g−1 h−1, respectively.